Burst that Bubble. Gastric Perforation from an Ingested Intragastric Balloon: A Case Report - Miriam Martinez; Khristopher Faiss; Neha Sehgal (Clinical Practice and Cases in Emergency Medicine)
Introduction: More than 40% of Americans are considered obese, resulting in annual healthcare costs estimated at $173 billion. 1, 2 Various interventions exist to address obesity including lifestyle modification, medications, and several surgical options. A novel ingestible intragastric balloon that self-deflates and is excreted approximately four months post-ingestion is being used in other countries such as Australia, Mexico, and several European countries. Currently, however, there are no US Food and Drug Administration-approved, commercially available options like this in the United States. Case Report: We present a case of a 31-year-old, obese male who presented to the emergency department for abdominal pain approximately 10 weeks after the ingestion of an inflatable balloon for weight loss treatment in Mexico. He was found to have a gastric perforation and required an emergent exploratory laparotomy. Conclusion: While ingestible, weight-loss balloons are not yet commercially available in the United States, emergency physicians may still encounter complications of such devices.